Schools of Indian and Iranian languages - E. L. Gladkova (Vestnik MGIMO-Universiteta)
Teaching Indian and Iranian and African languages is carried out at MGIMO since 1954. Today the Department of Indo-Iranian and African languages does the teaching of languages Hindi, Urdu, Bengali, Persian, Dari, Pashto, Tajik, Amharic, Swahili.